Disaster management in sub-Saharan Africa : policies, institutions and processes - Balgah, Roland Azibo; Kimengsi, Jude Ndzifon (Emerald Publishing Limited, 2022)
The global escalation of natural and human-induced disasters, and their future predicted occurrence is extremely worrying, especially in Sub-Saharan Africa (SSA). In addition to summarizing global disaster management frameworks, this book discusses the African Union's strategy for disaster risk reduction (AU-DRR), including country-specific cases, and explores the extent to which national policies resonate with AU-DRR. By combining reviews with empirical evidence, the chapters provide an in-depth analysis of disaster policy processes, institutions and arrangements in SSA, situating the sub-continent within overarching global and African instruments such as the Sendai Framework for Disaster Risk Reduction, and the African Union's Disaster Risk Reduction strategy. The book further provides novel insights which can enhance understanding of disaster risk reduction in Africa from a policy perspective. A combined analysis of all the chapters provides an interesting summary and information for creating disaster management policies for improved results in SSA. With an extensive glossary of terms and index, the book lends itself to specialized academics and students, but also to disaster management policy makers and practitioners and the occasional user.